Hitchin Pairs for non-compact real Lie groups - Gothen, PB (2016)
Hitchin pairs on Riemann surfaces are generalizations of Higgs bundles, allowing the Higgs field to be twisted by an arbitrary line bundle. We consider this generalization in the context of G-Higgs bundles for a real reductive Lie group G. We outline the basic theory and review some selected results, including recent results by Nozad and the author arXiv:1602.02712 [math.AG] on Hitchin pairs for the unitary group of indefinite signature U(p,q).